2017
DOI: 10.18632/oncotarget.20414
|View full text |Cite
|
Sign up to set email alerts
|

Secreted gelsolin desensitizes and induces apoptosis of infiltrated lymphocytes in prostate cancer

Abstract: Loss of immunosurveillance is a major cause of cancer progression. Here, we demonstrate that gelsolin, a constituent of ejaculate, induces apoptosis of activated lymphocytes in prostate cancer. Gelsolin was highly expressed in prostate cancer cells, and was associated with tumor progression, recurrence, metastasis, and poor prognosis. In vitro, secreted gelsolin inactivated CD4+ T cells by binding to CD37, and induced apoptosis of activated CD8+ T lymphocytes by binding to Fas ligand during cell contact depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 36 publications
(82 reference statements)
5
25
1
Order By: Relevance
“…We have previously demonstrated that the over-expression of gelsolin protects ovarian cancer cells against cisplatin-induced death and could be a potential target for treatment 26 . pGSN has also been implicated in pathological disease conditions such as prostate cancer, breast cancer, sepsis, arthritis, microbial infections, hemodialysis and other inflammatory disorders 22,2731 . Although pGSN is highly secreted in OVCA cells, its role in patients’ plasma has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that the over-expression of gelsolin protects ovarian cancer cells against cisplatin-induced death and could be a potential target for treatment 26 . pGSN has also been implicated in pathological disease conditions such as prostate cancer, breast cancer, sepsis, arthritis, microbial infections, hemodialysis and other inflammatory disorders 22,2731 . Although pGSN is highly secreted in OVCA cells, its role in patients’ plasma has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have reported a strong association between circulating pGSN levels and inflammation-associated clinical states, but their potential regulatory roles in relation to immune cells were only revealed recently. pGSN was reported to inactivate CD4+ T cells through CD37 signaling and to induce the apoptosis of activated CD8+ T cells through membrane-bound FasL [24]. Similarly, the observed lower circulating pGSN level in patients with HNC compared with in healthy controls could reflect their consumption by CD8+ T cells that triggered apoptosis.…”
Section: Discussionmentioning
confidence: 97%
“…pGSN expression is implicated in various pathological conditions, such as acute respiratory distress syndrome, sepsis, acute hepatic failure, myonecrosis [19][20][21], and various cancers [22,23]. Recently, the role of pGSN in apoptosis induction in tumor-infiltrating CD8+ T lymphocytes has been demonstrated through FasL binding in prostate cancer [24]. However, the significance of circulating pGSN levels in HNC prognosis and the relevant clinicopathological implications warrant elucidation.…”
Section: Introductionmentioning
confidence: 99%
“…GSN or Gelsolin gene encodes a protein that is involved in assembly and disassembly of actin filaments. Gelsolin has been attributed in prostate tumorigenesis and malignant transformation 56 , 57 . The C–C type chemokine 14 gene is known to induce targeted cell migration and is thought to play a role in carcinogenesis and metastasis of certain malignancies including breast cancer 58 , 59 .…”
Section: Discussionmentioning
confidence: 99%